FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PERUSAHAAN PUBLIK SEKTOR MANUFAKTUR TAHUN 2010-2013 (Students' Journal of Accounting and Banking, 2015)
This study aims to find empirical evidence and analyze the effect of profitability, liquidity, asset structure, systematic risk and the size of the company on thecapitalstructure. The population in this study are all companies registered manufacturing sector in Indonesia Stock Exchange 2010-2013 period. The samples in this study using purposive sampling method, which is based on certain criteria. Resulting in 227 observational data. Analysis of the data used in this research using descriptive statistics, testing normality of the data, the classical assumption test, multiple linear regression and goodness of fit test. Based on the results of research and discussion in this study, it can be concluded that the profitability of a significant negative effect on the capital structure. Liquidity significant negative effect, the structure of assets and systematic risk is not significant positive effect on capital structure, while the size of the company significant positive effect on the capital structure.Keywords: Profitability, Liquidity, Asset Structure, Systematic Risk, Firm Size and Capital Structure